Update culture and the afterlife of digital writing - Gallagher, John R., 1983- (Utah State University Press, 2019)
"Explores "neglected circulatory writing processes" to understand why and how digital writers compose, revise, and deliver arguments that undergo (sometimes constant) revision. Also looks at how digital writers respond to comments, develop a brand, and evolve their arguments-all post-publication"--Provided by publisher"--